Medical Ethics in Medical Students: State of the Art - Núñez Delgado, Rocío del Pilar (2023)
Background: Due to the diversity of ethical dilemmas, it is important that medical ethics be part of medical education to meet the professionalism standards of medical students. Objective: To define the state of the art of the relationship, uses and importance of medical ethics in medical students, absolving the following questions: What? Who? How? What is missing? Method: Clean search in PubMed / MEDLINE database on December 10, 2021, with the keywords: Medical Ethics, Medicine Students, Medicine and State of the art; Seven articles of one-year-old were obtained with respect to the date of the search; which were organized, cataloged, analyzed, summarized and determined important points for its presentation. Result: Medical ethics is closely related, it also has several uses and is very important in the training of medical students. Conclusion: Medical ethics must be part of the curriculum in Universities and Medical Colleges in an imperative way.